Pembelajaran Berbantuan Geogebra Berdasarkan Struktur Kognitif Manusia - Nabuasa, Adit; Lakusa, Sefnad Anovelthon Meinhart; Blegur, Irna Karlina Sensiana (Pendidikan Matematika FKIP Universitas Mataram, 2023)
In the current curriculum in Indonesia, students are the center of learning and teachers are only facilitators. Therefore, it is necessary to choose the right learning strategies and media so that learning activities can take place effectively and efficiently. The choice of learning strategies and media must pay attention to human cognitive structure. Apart from that, improving the quality of mathematics learning also requires technological assistance that is appropriate to current developments. With the help of technology, students will more easily visualize shapes and understand concepts in the material being taught. One media that can answer this is Geogebra. This article is a literature study that aims to discuss learning based on human cognitive structure. Further examples of the application of geogebra-assisted learning based on human cognitive structures are also discussed in this article.